140k views
1 vote
i need help with a math problem it says solve for t: -3(t - 2) + 7t=9t-9 can you show all the work please​

User Sophi
by
5.4k points

2 Answers

4 votes

Answer:

t = 3.

Explanation:

-3(t - 2) + 7t = 9t - 9 Distribute the -3 over the parentheses:

-3t + 6 + 7t = 9t - 9 Subtract 9t from both sides:

-3t - 9t + 7t + 6 = -9 Subtract 6 from both sides:

-3t - 9t + 7t = -9 - 6

-5t = -15

t = -15/-5

t = 3 (answer).

User MrScf
by
6.3k points
2 votes

Answer:

t = 3

Explanation:

Given

- 3 (t - 2) + 7t = 9t - 9 ← distribute left side and simplify

- 3t + 6 + 7t = 9t - 9

4t + 6 = 9t - 9 ( subtract 9t from both sides )

- 5t + 6 = - 9 ( subtract 6 from both sides )

- 5t = - 15 ( divide both sides by - 5 )

t = 3

User Bravohex
by
5.1k points